A clearance measurement system based on on-component multilayer tri-axial capacitive probe. (August 2018) - Addabbo, Tommaso; Bertocci, Francesco; Fort, Ada; Mugnaini, Marco; Panzardi, Enza; Vignoli, Valerio; Cinelli, Chiara
Highlights: A clearance measurement system based on an a printed "on-component" triaxial capacitive probe is proposed. The system allows for static and dynamic distance measurements. Two front-end circuits are described: linear distance-voltage and capacitance-voltage converters. A theoretical analysis of the measurement system performance is provided and experimentally verified. Abstract: In this paper the authors propose the design of a complete measurement system of clearance based on an 'on-component' triaxial capacitive probe for static and dynamic measurement of distance. The capacitive probe is designed to be deposited onto machinery components or complex structures and is aimed at reducing the impact of probe mounting on the monitored component. The problem is discussed from a theoretical point of view and then supported by the realization of a sensor prototype in screen printed technology and of two possible and alternative conditioning systems. The results prove the feasibility of this innovative measurement system.